Psychometric properties of diabetic patient's self-care scale in Iranian population (DSCS-I): an exploratory factor analysis study - Mehran Alijanzadeh; Sima Hashemipour; Fereshteh Attaran; Samira Saremi; Leyla Modaresnia; Hamidreza Ghafelehbashi; Sahar Jalili; Saba Alipour; Zainab Alimoradi (Hamadan University of Medical Sciences, 2024)
Background and Objective: Self-care is one of the best and most cost-effective measures to deal with diabetes that has attracted the attention of several health planners today. The current study aimed to perform a psychometric analysis of the Diabetes Self-Care Scale-I (DSCS-I) in Qazvin medical centers in Iran. Materials and Methods: The present study was methodological. The statistical population consisted of all patients in the medical centers of Qazvin city. The sample size was determined to be 256 people. After collecting the data, they were subjected to exploratory factor analysis with the principal component analysis method. Data were analyzed in SPSS22 software. Kaiser-Meyer and Bartlett's tests were used to measure the suitability of the sample and the significance of the results. Results: The mean age of the participants was 59.12±11.14 years, and the mean years of diabetes was 10.76±7.55. Based on the results of exploratory factor analysis, self-care of diabetic people was observed in four factors, namely healthy diet, physical activity, blood sugar monitoring, and foot health monitoring. The results showed that four explanatory factors of self-care could explain 95.22% of the variance of self-care in diabetic patients. Conclusion: The psychometric analysis of the DSCS-I in the Iranian population showed that this tool had very good validity and reliability. Therefore, it is necessary to use this scale to check the self-care status of diabetic patients.